How DNA and RNA Viruses Exploit Host Chaperones to Promote Infection - Kaitlyn Speckhart; Jeffrey M. Williams; Billy Tsai (Viruses, 2021)
To initiate infection, a virus enters a host cell typically via receptor-dependent endocytosis. It then penetrates a subcellular membrane, reaching a destination that supports transcription, translation, and replication of the viral genome. These steps lead to assembly and morphogenesis of the new viral progeny. The mature virus finally exits the host cell to begin the next infection cycle. Strikingly, viruses hijack host molecular chaperones to accomplish these distinct entry steps. Here we highlight how DNA viruses, including polyomavirus and the human papillomavirus, exploit soluble and membrane-associated chaperones to enter a cell, penetrating and escaping an intracellular membrane en route for infection. We also describe the mechanism by which RNA viruses—including flavivirus and coronavirus—co-opt cytosolic and organelle-selective chaperones to promote viral endocytosis, protein biosynthesis, replication, and assembly. These examples underscore the importance of host chaperones during virus infection, potentially revealing novel antiviral strategies to combat virus-induced diseases.